2012
DOI: 10.1063/1.4723867
|View full text |Cite
|
Sign up to set email alerts
|

Many competing ceria (110) oxygen vacancy structures: From small to large supercells

Abstract: We present periodic "DFT+U" studies of single oxygen vacancies on the CeO 2 (110) surface using a number of different supercells, finding a range of different local minimum structures for the vacancy and its two accompanying Ce(III) ions. We find three different geometrical structures in combination with a variety of different Ce(III) localization patterns, several of which have not been studied before. The desired trapping of electrons was achieved in a two-stage optimization procedure. We find that the surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
58
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 56 publications
8
58
2
Order By: Relevance
“…Some researchers reported that the two excess electrons prefer to localize on two Ce atoms that are the nearest neighbor (NN) to the vacancy [15,16,29,30,[34][35][36][37][38][39], while others [40,41,42] suggested that having the Ce 3+ on the next-nearest neighbor (NNN) sites is energetically more favorable over the NN configuration.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some researchers reported that the two excess electrons prefer to localize on two Ce atoms that are the nearest neighbor (NN) to the vacancy [15,16,29,30,[34][35][36][37][38][39], while others [40,41,42] suggested that having the Ce 3+ on the next-nearest neighbor (NNN) sites is energetically more favorable over the NN configuration.…”
Section: Introductionmentioning
confidence: 99%
“…For the oxygen vacancy, the excess electrons are localized on individual Ce atoms, turning two Ce 4+ into two Ce 3+ species, which, by Coulomb attraction, sit near to the vacancy [29][30][31][32][33][34][35][36][37][38][39][40][41][42]. The results of DFT+U studies are largely dependent on the U value, bringing some uncertainty to the results and raising questions on what value of U should be used to describe the properties of perfect and reduced CeO 2 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[5] The most commonly studied defect on CeO 2 surfaces is the O vacancy, due to its importance for describing catalysis of CeO 2 . [15][16][17][18] Upon the formation of a neutral O vacancy, excess electrons are localized onto Ce(IV) ions, reducing them to Ce(III). In Kröger-Vink notation this is given as:…”
Section: Introductionmentioning
confidence: 99%